The Cranberry Extract Oximacro® Exerts in vitro Virucidal Activity Against Influenza Virus by Interfering With Hemagglutinin - Luganini, Anna; Terlizzi, Maria E.; Catucci, Gianluca; Gilardi, Gianfranco; Maffei, Massimo E.; Gribaudo, Giorgio (Frontiers in Microbiology, 2018)
The defense against influenza virus (IV) infections still poses a series of challenges. The current antiviral arsenal against influenza viruses is in fact limited; therefore, the development of new anti-influenza strategies effective against antigenically different viruses is an urgent priority. Bioactive compounds derived from medicinal plants and fruits may provide a natural source of candidates for such broad-spectrum antivirals. In this regard, cranberry (Vaccinium macrocarpon Aiton) extracts on the basis of their recognized anti-adhesive activities against bacteria, may provide potential compounds able to prevent viral attachment to target cells. Nevertheless, only few studies have so far investigated the possible use of cranberry extracts as an antiviral tool. This study focuses on the suitability of a cranberry extract as a direct-acting anti-influenza compound. We show that the novel cranberry extract Oximacro® inhibits influenza A and B viruses (IAV, IBV) replication in vitro because of its high content of A-type proanthocyanidins (PAC-A) dimers and trimers. Mechanistic studies revealed that Oximacro® prevents attachment and entry of IAV and IBV into target cells and exerts a virucidal activity. Oximacro® was observed to interact with the ectodomain of viral hemagglutinin (HA) glycoprotein, thus suggesting the interference with HA functions and a consequent loss of infectivity of IV particles. Fluorescence spectroscopy revealed a reduction in the intrinsic fluorescence of HA protein after incubation with purified dimeric PAC-A (PAC-A2), thus confirming a direct interaction between HA and Oximacro® PAC-A2. In silico docking simulations further supported the in vitro results and indicated that among the different components of the Oximacro® chemical profile, PAC-A2 exhibited the best binding propensity with an affinity below 10 nM. The role of PAC-A2 in the anti-IV activity of Oximacro® was eventually confirmed by the observation that it prevented IAV and IVB replication and caused the loss of infectivity of IV particles, thus indicating PAC-A2 as the major active component of Oximacro®. As a whole, these results suggest Oximacro® as a potential candidate to create novel antiviral agents of natural origin for the prevention of influenza virus infections.